Oppression and resistance : structure, agency, transformation - Musolf, Gil Richard, 1951- (Bingley, U.K. : Emerald Publishing Limited, 2017)
Oppression and resistance dialectically envelop everyday life, for both the privileged and the oppressed. The disenfranchised live under regimes in which repression ranges from brutal to institutionally subtle. The privileged socially reproduce their rule through ideology that justifies and policy that institutionalizes subjugation. However, rejecting depression, detachment, and disaffection that emerges from surviving ruling-class regimes, many previously dispirited, instead, choose defiance. They engage in subjectivity struggles by crafting critical consciousness, refusing to be dupes to ideology that represents them as inferior. They undertake social struggles demanding policy that dismantles institutional discrimination and that enhances opportunities for learning and achievement. The exploited, as best as they can in regimes of ruling class and white male supremacy, reconstruct their selves and, it is hoped, transform society. The qualitative studies that comprise this edited collection, present a structure-and-agency perspective, broadly defined, that constitutes the best sociological lens through which to understand oppression and resistance. Contributors interrogate various aspects of oppression and resistance, from the personal to the institutional, exploring situations in which the structure of oppression was insurmountable and illustrating cases in which agency was able to transform either individual or group identity.
Prelims -- Oppression and resistance: a structure-and-agency perspective -- Behind closed doors: organizational secrecy, stigma, and sex abuse within the Catholic Church --'Black Man/White Tower' : a performative film autocritography -- Transforming identities of illness through aesthetic narrative collaboration -- Power, emergence, and the meanings of resistance: open access scholarly publishing in Canada -- Collective and community work in Senegal: Resisting colonial and neoliberal models of economic development -- Time to defy: the use of temporal spaces to enact resistance -- Dupe, schemer, mother: navigating agency and constraint at work --'They expect you to be better': mentoring as a tool of resistance among black fraternity men -- PUblic sociology and symbolic interactionism: participatory research and writing culture with a southern Native American Tribe -- About the authors -- Index.
Includes index.
Includes bibliographical references.
Keywords: Social sciences -- Philosophy; Sociology; Social Science -- Sociology / Social Theory; Social theory